The Relationship between Physical Dating Violence and Alcohol and Drug Use among High School Students in an Urban Florida County - Stacey B. Griner; Michele Johnson Moore; Kristina Wilson (University of North Florida, 2018)
Physical dating violence (PDV) is associated with a number of serious behavioral and psychological consequences for adolescents who have been victimized. However, there are few studies investigating the relationship between PDV and alcohol and drug use specifically among high school students in Florida. This study analyzes data from the 2013 Youth Risk Behavior Survey in an urban school district in Florida. Alcohol use, drug use, and sociodemographic factors were significantly associated with PDV. After controlling for individual factors, odds of experiencing PDV were higher among those who reported current alcohol use (aOR: 2.38, [95% CI 1.53-3.69]) and those who reported ever using methamphetamines (aOR: 2.87 [95% CI 1.14-7.23]) than those who did not. We discuss the implications for research to improve understanding of the antecedents, health impact, and methods of prevention for alcohol and drug use and PDV among Florida high school students.